MiRNA-related metastasis in oral cancer: moving and shaking - Meghdad Eslami; Saba Khazeni; Xaniar Mohammadi Khanaghah; Mohammad Hossein Asadi; Mohamad Amin Ansari; Javad Hayati Garjan; Mohammad Hassan Lotfalizadeh; Mobina Bayat; Mohammad Taghizadieh; Seyed Pouya Taghavi; Michael R Hamblin; Javid Sadri Nahand (Cancer Cell International, 2023)
Abstract Across the world, oral cancer is a prevalent tumor. Over the years, both its mortality and incidence have grown. Oral cancer metastasis is a complex process involving cell invasion, migration, proliferation, and egress from cancer tissue either by lymphatic vessels or blood vessels. MicroRNAs (miRNAs) are essential short non-coding RNAs, which can act either as tumor suppressors or as oncogenes to control cancer development. Cancer metastasis is a multi-step process, in which miRNAs can inhibit or stimulate metastasis at all stages, including epithelial-mesenchymal transition, migration, invasion, and colonization, by targeting critical genes in these pathways. On the other hand, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), two different types of non-coding RNAs, can regulate cancer metastasis by affecting gene expression through cross-talk with miRNAs. We reviewed the scientific literature (Google Scholar, Scopus, and PubMed) for the period 2000–2023 to find reports concerning miRNAs and lncRNA/circRNA-miRNA-mRNA networks, which control the spread of oral cancer cells by affecting invasion, migration, and metastasis. According to these reports, miRNAs are involved in the regulation of metastasis pathways either by directly or indirectly targeting genes associated with metastasis. Moreover, circRNAs and lncRNAs can induce or suppress oral cancer metastasis by acting as competing endogenous RNAs to inhibit the effect of miRNA suppression on specific mRNAs. Overall, non-coding RNAs (especially miRNAs) could help to create innovative therapeutic methods for the control of oral cancer metastases.